2010
DOI: 10.1590/s0102-695x2010000100025
|View full text |Cite
|
Sign up to set email alerts
|

Hypotriglyceridemic effect of Morus alba L., Moraceae, leaves in hyperlipidemic rats

Abstract: RESUMO: "Efeito hipotrigliceridêmico de folhas de Morus alba L., Moraceae, em ratos hiperlipidêmicos". As folhas de amoreira branca Morus alba L., Moraceae, são utilizadas no Brasil na medicina popular para tratar febre, como protetor do fígado, para baixar a pressão e o colesterol. O extrato aquoso de folhas de M. alba foi administrado via oral através de gavagem em ratos hiperlipidêmicos com uma dieta enriquecida com colesterol (1%) com uma dose de 150 mg/kg/dia por quatorze dias que reduziu significativamen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…The addition of mulberry extract to the diet is preventing the inflammatory process. Our results are in line with Zeni and Dall'Molin who showed that the aqueous mulberry leaf extract leads to inhibition of liver damage in hyperlipidaemic rats [39]. In contrast, Katsube et al did not observe similar effect in their studies on rats [7].…”
Section: In Vivo Analysis Of M Alba Leaf Extractsupporting
confidence: 91%
“…The addition of mulberry extract to the diet is preventing the inflammatory process. Our results are in line with Zeni and Dall'Molin who showed that the aqueous mulberry leaf extract leads to inhibition of liver damage in hyperlipidaemic rats [39]. In contrast, Katsube et al did not observe similar effect in their studies on rats [7].…”
Section: In Vivo Analysis Of M Alba Leaf Extractsupporting
confidence: 91%
“…The aqueous extract of Mulberry leaves at a dose of 150 mg/kg/day, for 14 days, significantly decreased the triglycerides level by 55.01% in rats on high cholesterol diet (26) .…”
Section: Hypolipidemic and Anti-obesity Effectsmentioning
confidence: 91%
“…Moracin isolated from the leaves of Morus alba inhibited lipid peroxidation which strongly indicated its role as scavenger (26) .…”
Section: Hypolipidemic and Anti-obesity Effectsmentioning
confidence: 92%
“…Besides the effective compounds of mulberry leaves they are nontoxic and have natural therapeutic properties because they act as antioxidants, anti-stress agents and immunoenhancers, and have cholesterol-lowering and nephro-and hepato-protective properties (Yang et al, 2012;Devi et al, 2013). Numerous researches demonstrated that anthocyanins and flavonoids present in mulberry leaves can protect against atherosclerotic and coronary heart diseases via removing the metabolic free radicals, inhibiting the LDL oxidation and their hypolipidemic and hypocholesterolemic properties (Zeni & Molin, 2010;Valacchi et al, 2014). Also, Abd El-Hady et al (2017) who observed that decreased blood malondialdehyde and increased glutathione levels as Glutathione boosts white jas.ccsenet.org Vol.…”
Section: Blood Parametersmentioning
confidence: 99%